Bumblebees Perform Well-Controlled Landings in Dim Light - Reber, Therese; Dacke, Marie; Warrant, Eric; Baird, Emily (Frontiers in Behavioral Neuroscience, 2016)
To make a smooth touchdown when landing, an insect must be able to reliably control its approach speed as well as its body and leg position – behaviors that are thought to be regulated primarily by visual information. Bumblebees forage and land under a broad range of light intensities and while their behavior during the final moments of landing has been described in detail in bright light, little is known about how this is affected by decreasing light intensity. Here, we investigate this by characterizing the performance of bumblebees, B. terrestris, landing on a flat platform at two different orientations (horizontal and vertical) and at four different light intensities (ranging from 600 lx down to 19 lx). As light intensity decreased, the bees modified their body position and the distance at which they extended their legs, suggesting that the control of landing in these insects is visually mediated. Nevertheless, the effect of light intensity was small and the landings were still well controlled, even in the dimmest light. We suggest that the changes in landing behavior that occurred in dim light might represent adaptations that allow the bees to perform smooth landings across the broad range of light intensities at which they are active.